2007
DOI: 10.1007/s10562-007-9299-y
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Cerium–Manganese Mixed Oxides for Oxidation Catalysis

Abstract: Cerium-manganese mixed oxides with compositions of Ce 0.5 Mn 0.5 O 1.75 and Ce 0.8 Mn 0.2 O 1.9 were prepared by the citric-acid (Pechini) method and their catalytic properties were compared to CeO 2 and Mn 2 O 3 . The mixed oxides exhibited higher specific rates than either CeO 2 or Mn 2 O 3 for oxidation of both methane and n-butane. While XRD measurements of the mixed oxides suggested that the materials had primarily the fluorite structure, oxygen isotherms, measured by coulometric titration at 973 K, exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 35 publications
(51 reference statements)
1
30
0
Order By: Relevance
“…(2) and (3). The unsatisfactory attempts to cycle the pure manganese oxides are attributed to kinetics constraints in line with the poor oxygen mobility in manganese oxides [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…(2) and (3). The unsatisfactory attempts to cycle the pure manganese oxides are attributed to kinetics constraints in line with the poor oxygen mobility in manganese oxides [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the reducibility of the catalyst should be optimum for high activity. There have been investigations on the effect of redox properties of the support on the activity toward WGS and other redox reactions 33, 34. Similarly, Baldychev et al35 observed high rates of WGS with Fe supported over alumina and zirconia.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the coulometric titration cell and apparatus has been reported previously [21][22][23][24][25] and only a brief description will be given here. Approximately 0.4 g of sample was loaded into a yttria stabilized zirconia (YSZ) tube, which was sealed at one end by an O 2 sensor consisting of a dense YSZ wafer with porous Ag electrodes on both its inner and outer surfaces.…”
Section: Measurement Of Redox Isothermsmentioning
confidence: 99%